2006
DOI: 10.1093/hmg/ddl404
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-2 mediates physical and functional interactions between polycystin-2 and fibrocystin

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in PKD1, encoding polycystin-1 (PC1), or PKD2 (polycystin-2, PC2). Autosomal recessive PKD (ARPKD) is caused by mutations in PKHD1, encoding fibrocystin/polyductin (FPC). No molecular link between ADPKD and ARPKD has been determined. Here, we demonstrated, by yeast two-hybrid and biochemical assays, that KIF3B, a motor subunit of kinesin-2, associates with PC2 and FPC. Co-immunoprecipitation experiments using Madin-Darby canine kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 46 publications
3
85
0
1
Order By: Relevance
“…44 Fibrocystin is localized to the cilium and has been recently found in the same protein complex as PC2. 18,45 This suggests that fibrocystin and the autosomal dominant disease proteins may share a common pathway. We addressed the question whether lack of PC1 or PC2 might influence location or level of fibrocystin expression by examining fibrocystic expression in orthologous cystic models because of mutation in either Pkd1 or Pkd2.…”
Section: Discussionmentioning
confidence: 99%
“…44 Fibrocystin is localized to the cilium and has been recently found in the same protein complex as PC2. 18,45 This suggests that fibrocystin and the autosomal dominant disease proteins may share a common pathway. We addressed the question whether lack of PC1 or PC2 might influence location or level of fibrocystin expression by examining fibrocystic expression in orthologous cystic models because of mutation in either Pkd1 or Pkd2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that polycystin-1, polycystin-2, and fibrocystin localize to the primary cilium. These three proteins appear to be in the same complex (47,48). Furthermore, these proteins have been proposed to have a role in mediating flow dependent mechanosensation (47,(49)(50)(51)(52)(53)(54), suggesting a common pathway in cyst development.…”
Section: Inherited Polycystic Kidney Diseasesmentioning
confidence: 99%
“…Several in vitro studies from our group and others have shown that FPC and PC2 co-localize to the basal bodies/primary cilia of renal epithelial cells and are able to form a molecular complex and function in the same signaling pathway. 31,36 For further validation of this finding in vivo, the phenotypic effects of transheterozygosity for Pkhd1 and Pkd2 were examined. We intercrossed Pkhd1 ϩ/Ϫ and Pkd2 ϩ/Ϫ mutant mice to produce cohorts of age-matched littermates.…”
Section: Lack Of Fpc Exhibits Aberrant Ciliogenesis In the Renal Epitmentioning
confidence: 99%
“…31,36 In addition, other polyclonal antibodies and mAb were purchased: Anti-acetylated ␣-tubulin, anti-␥-tubulin, anti-␤-actin, anti-Flag, and anti-HA mAb (Sigma, St. Louis, …”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation